An instantly usable paper-based screen-printed solid-state KCl/Ag/AgCl reference electrode with long-term stability1. Issue 19 (7th October 2015) - Shitanda, Isao; Komoda, Masato; Hoshi, Yoshinao; Itagaki, Masayuki
<x xml:space="preserve">Abstract</x> An instantly usable screen-printed paper-based Ag/AgCl electrode was fabricated for use as a cost-effective disposable reference electrode.